Tomografía computarizada de haz cónico para el diagnóstico de la reabsorción radicular externa asociada al tratamiento de ortodonci - Burgos-Urey, Mariela (2020)
External root resorption (ERR) is a highly prevalent, multifactorial problem frequently associated with orthodontic treatment. Treatment is complex due to the lack of solid knowledge regarding predisposing factors, systematic management for diagnosis and follow-up protocols or thefundamental theoretical bases of adequate imaging tools for each situation. This review describes the indications of the use of cone beam computed tomography (CBCT) and the factors related to its development and the characteristics of the techniques used in the diagnosisand monitoring of ERR in orthodontics. We compared the advantages and disadvantages of CBCT based on the risk/benefits. Methods: We have reviewed and summarized the information and the risk factors available on ERR in orthodontics and the use of CBCT in the diagnosis and follow-up of ERR with the aim of developing a management protocol. Likewise, CBCT is compared with other imaging techniques frequently used in ERR. The articles reviewed in this study coincide in terms of the advantages of precision of CBCT in the detection and linear and volumetric measurement of ERR associated with orthodontics over two-dimensional techniques. However, CBCT cannot completely replace other imaging techniques since its effectiveness is not significantly greater in cases with moderate ERR compromise. The use of CBCT should be optimized following specific criteria for its application.